Estudo de catalisadores X% Ni-CeZrO2 na reação de reforma do metano com CO2 e H2O - Diniz, Alexander Ferreira (2004)
The main goal of this thesis was studying the x%Ni/CeZrO2 catalysts (x: % =1,5; 5 and 10) in the dry and steam coupled-reforming. All the catalysts were prepared by successive wetness impregnations of the support (CeZrO2) with an aqueous solution of nickel nitrate, dried, and calcined at 500°C. The catalytic sites were characterized by temperature programmed desorption of CO2 (TPD-CO,) and of H2 (TPD-H2), and also by “in-situ” X-rays (DRX) diffraction. The catalytic tests were carried out at 800°C, after a reduction of 12mg of catalyst during 3 hours at 500°C, using a reaction mixture containing (CH4:H2O:CO2) equal to (3:2:1). The profiles of TPD-CO2 showed the presence of moderate strength redox/basic sites. They also indicate the presence of some strong sites. An homogeneous solid solution between cerium and zirconium oxides was stated in all catalysts, whether they were calcined or reduced. A small displacing of 0.2° after reduction indicated a little distortion of the cubic crystalline structure, caused by the partial reduction of the mixed oxide. The CH4 reforming with CO2 and H2O led to a synthesis gas formation with an ideal ratio for the Fischer-Tropsch synthesis. Redox sites play an important role in the catalyst stability and activity by a bifunctional mechanism, in which they are responsible for the decomposition of CO2 and H2O and fumish molecular oxygen for carbon removable. Two types of hydrogen-free carbon deposited on the surface were observed after the reforming reactions: graphitic and/or amorphous, that is oxidized at high temperatures, and a filamentous one, oxidized at low temperaturas.